(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
According to the research results, the content of nutrients was different. Thus, the nitrogen content was the highest on the N background30P60 – 12,5 mg/100 g of soil, which can be characterized as average, which was enough to form a high level of crops. According to the results of the research, it was found that the crop of peas was determined both by the conditions of moistening and by the fertilization system. Thus, when growing peas without irrigation on a background without fertilizers, the productivity was the lowest and counted 3.11 t/ha. Against the background of P60 crop increased by 0.35 t/ha, or by 10.9% compared to the background without fertilizers. In the background N30P60 also noted a tendency to increase productivity - its level increased to 3.57 t/ha, which is 0.46 t/ha or 14.8% more than on an unfertilized background. It should be said that on irrigation, the increase from the application of fertilizers against the background of N30P60 was quite significant and was equal to 0.63 t/ha, or 16.5% compared to the background without fertilizers. Comparing the crop of peas under different conditions of moisture, it was found that the highest yield was observed under irrigation on the background of N30P60, which is 0.87 t/ha more than when grown in non-irrigated conditions. Research has established that such elements of the structure of the pea harvest as the number of plants, the number of beans and the weight of 1000 seeds determine the level of the harvest. Due to irrigation and fertilization, the number of plants increased by 9-11 plants/m2 and was 111-115 pcs./m2 depending on the power background. The use of fertilizers had a positive effect on the number of beans. Yes, on irrigation against the background of R60 та N30P60 the number of beans increased by 53 pcs./m2 and 152 pieces/m2 respectively, compared to the background without fertilizers, and the yield on the N background30P60 increased by 0.63 t/ha. During the pea growing season, soil moisture was lower than normal even with irrigation, which to some extent restrained physiological processes in the plant, thereby reducing the productivity of pea crops. On irrigation, a decrease in protein content was noted, and on the background without fertilizers, the difference was the most significant and amounted to 3.6%. High protein crops among different cultivation options are provided by the option of using irrigation in the background N30P60 - protein collection is 1.23 t/ha. During the harvesting of peas, certain grain losses were noted, which after disking and sprinkler irrigation produced 10.5 t/ha of vegetative mass. The given mass was disked into the soil, which ensured the entry of organic matter into the soil, which is equivalent to 17.8 kg of nitrogen, 3.2 kg of phosphorus and 20.5 kg of potassium, respectively.